Legionellosis in Patients With Cancer: A Retrospective Observational Study, 2005–2014. Issue 4 (July 2015) - Yacoub, Abraham; Sadic, Edin; Flynn, Alexandra; Katayama, Mitsuya; Greene, John
Abstract : Background: Legionella species cause severe pneumonia in the immunocompromised population, especially those with cell-mediated immunodeficiency. However, the varied clinical and radiographic presentation of Legionnaires disease can make diagnosis very difficult, which can result in a delay of appropriate therapy. For that reason, we performed this study to review the characteristics of Legionella pneumonia in immunocompromised patients with underlying cancer. Methods: The study was a retrospective chart review of 11 patients with Legionella pneumonia at the Moffitt Cancer Center diagnosed between March 2005 and February 2014. The patients were identified on the basis of a positive bronchoalveolar lavage culture for Legionella and/or a positive Legionella urine antigen. Summarized host characteristics included underlying malignancy, absolute neutrophil count, and absolute lymphocyte count at the time of diagnosis as well as the computed tomographic chest imaging findings. Results: Of the 11 patients included, 10 had Legionella pneumophila and 1 had L. feeleii . Nine (81.8%) of the 11 patients had a hematologic malignancy and 2 (18.2%) of the 11 patients had a solid organ tumor. One (9.0%) of the 11 patients had an underlying lung disease. At the time of the diagnosis, 3 (27.2%) of the 11 patients were neutropenic (absolute neutrophil count, <500 cells/mm 3 ) and 8 (72.7%) of the 11 patients were lymphopenic (absolute lymphocyte count, <1500 cells/mm 3 ). Four (36.3%) of the 11 patients had bilateral pneumonia. Three (27.2%) of the 11 patients had nodular consolidation. However, only 2 (18%) of the 11 patients were found to have consolidation along with ground-glass opacity. All patients were treated with levofloxacin. Seven (63.6%) of the 11 patients adequately responded to the therapy, 1 (9.0%) patient died because of pneumonia, and 3 (27.3%) patients died because of the underlying cancer. Conclusions: Legionnaire disease remains a life-threatening illness in patients with cancer. Our study found that most patients are lymphopenic, with multifocal consolidation in 2 of 3 patients. In addition, nodular opacities on computed tomographic imaging were described in more than one third of our patients, which resembles a mold pneumonia. All the cases that were thought to be a mold pneumonia were diagnosed as Legionella by bronchoalveolar lavage culture or the Legionella urine antigen, emphasizing the need for heightened awareness and testing for this pathogen.